Exploring education : an introduction to the foundations of education - Sadovnik, Alan R.; Cookson, Peter W.; Semel, Susan F., 1941- (New York : Routledge, 2012)
'This much-anticipated fourth edition of Exploring Education offers an alternative to traditional foundations texts by combining a point-of-view analysis with primary source readings. Pre- and in-service teachers will find a solid introduction to the foundations disciplines--history, philosophy, politics, and sociology of education--and their application to educational issues, including school organization and teaching, curriculum and pedagogic practices, education and inequality, and school reform and improvement. This edition features substantive updates, including the addition of discussion on the neo-liberal educational policy and recent debates about teacher evaluation, updated data and research, and new readings by leading researchers, such as Diane Ravitch, Robert Dreeben, Pedro Noguera and Helen F. Ladd.At a time when foundations of education are marginalized in many teacher education programs and teacher education reform pushes scripted approaches to curriculum and instruction, Exploring Education helps teachers to think critically about the'what' and'why' behind the most pressing issues in contemporary education.'--
The limits and promises of education : toward reflective practitioners -- The politics of education : conservative, liberal, and radical perspectives -- The history of education -- The sociology of education -- The philosophy of education and its significance for teachers -- Schools as organizations and teacher professionalization -- Curriculum, pedagogy, and the transmission of knowledge -- Equality of opportunity and educational outcomes -- Explanations of educational inequality -- Educational reform and school impovement.
Includes bibliographical references and index.
Keywords: Education -- United States; Educational sociology -- United States; Education -- United States -- Philosophy